IMPLEMENTING INTEGRATED STRATEGIES IN ENGLISH CLASSES: CHALLENGES AND OUTCOMES - Hamroyeva Zilola Hikmatovna; Yuldasheva Gulmira Kamolovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article explores the effectiveness of integrated education for students in English language classes, examining how a holistic approach to teaching can enhance language and cognitive development. Integrated education refers to the incorporation of diverse teaching strategies that blend language learning with content instruction, promoting critical thinking, problem-solving, and collaborative learning. The study reviews various pedagogical frameworks, including Content and Language Integrated Learning and task-based approaches, to assess their impact on student engagement, language acquisition, and academic performance. Drawing from empirical research and case studies, the article highlights the benefits and challenges of integrating subjects and language learning, suggesting that such an approach fosters a more inclusive, interactive, and student-centered educational environment. Ultimately, the findings demonstrate that integrated education in English classes contributes to improved learning outcomes, greater student motivation, and a deeper understanding of both language and content.